Subcellular localization and post-secretory targeting of TgPI, a serine proteinase inhibitor from Toxoplasma gondii - Pszenny, Viviana (2002)
Fil: Pszenny, Viviana. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas. Departamento de Parasitología; Argentina.